SOWING TIME AND CULTIVARS SELECTION MATTERS TO ENHANCE SOYBEAN PRODUCTIVITY UNDER CONTRASTING AGRO-ECOLOGICAL ZONES IN PAKISTAN - FARINA SHAHEEN; Imran Mehmood; Muhammad Farooq; Saeed Ahmad Asad (Journal of Animal and Plant Sciences, 2025)
Soybean (Glycine max (L.) Merr.), hailed as the "golden bean," is a globally significant crop valued for its high nutritional value, soil-enriching nitrogen fixation capacity, and wide-ranging applications in food, feed, and industry. Despite its higher yield potential, soybean cultivation in Pakistan remains limited, primarily due to erratic climatic conditions, suboptimal agronomic farming practices, and restricted access to quality seed. This study aimed to evaluate the interactive effects of planting time, cultivar selection, and climatic conditions on soybean growth and yield under contrasting agro-ecological zones. Field experiments were carried out over two consecutive seasons: 2021 and 2022 under rainfed conditions in Chakwal and irrigated conditions in Swat. Two soybean cultivars, NARC-2 and NARC-21 were sown on June 5, June 25, and July 15 using a randomized complete block design with a split plot arrangement. Early planting on 5 June conferred a significant advantage, as delaying sowing on 15 July resulted in substantial reductions in physiological and yield parameters, including a 51.01% decline in leaf area index (LAIX), a 56.76% decrease in total dry matter (TDM), and a 56.83% reduction in grain yield (GY). NARC-21 consistently outperformed NARC-2, especially at the Swat location, where adequate irrigation and higher solar radiation contributed to improved physiological development and yield. Early sowing (5 June) of cultivar NARC-21 under irrigated conditions exhibited >50% higher yield than late sowing. Conversely, delayed planting shortened the growing season by 16.7%, resulting in limited biomass accumulation and grain yield. Climatic analysis revealed strong positive correlations between soybean performance, total solar radiation, and optimal temperature regimes, confirming the crop’s sensitivity to planting time and environmental cues. Our results indicate that NARC-21 consistently outperformed NARC-2 across all sowing dates, with higher yields recorded at both locations. Overall, yield was greater at Swat than Chakwal, highlighting the importance of cultivar adaptability and favorable agro-environmental conditions. These findings underscore the need for climate-smart cultivar selection and policy support to promote early planting strategies across Pakistan’s agro-ecological zones.
Keywords: Planting time; agro-ecological zones; rainfed agriculture; irrigated conditions; phenology; climate variability